Ganglioside Extraction, Purification and Profiling - Porter, Mitchell J. (J Vis Exp, 2021)
Gangliosides are glycosphingolipids that contain one or more sialic acid residues. They are found on all vertebrate cells and tissues but are especially abundant in the brain. Expressed primarily on the outer leaflet of the plasma membranes of cells, they modulate the activities of cell surface proteins via lateral association, act as receptors in cell-cell interactions and are targets for pathogens and toxins. Genetic dysregulation of ganglioside biosynthesis in humans results in severe congenital nervous system disorders. Because of their amphipathic nature, extraction, purification, and analysis of gangliosides require techniques that have been optimized by many investigators in the 80 years since their discovery. Here, we describe bench-level methods for the extraction, purification, and preliminary qualitative and quantitative analyses of major gangliosides from tissues and cells that can be completed in a few hours. We also describe methods for larger scale isolation and purification of major ganglioside species from brain. Together, these methods provide analytical and preparative scale access to this class of bioactive molecules.